2011
DOI: 10.1007/s10714-011-1225-3
|View full text |Cite
|
Sign up to set email alerts
|

f (R) black holes

Abstract: We study the stability of f (R)-AdS (Schwarzschild-AdS) black hole obtained from f (R) gravity. In order to resolve the difficulty of solving fourth order linearized equations , we transform f (R) gravity into the scalar-tensor theory by introducing two auxiliary scalars. In this case, the linearized curvature scalar becomes a dynamical scalaron, showing that all linearized equations are second order. Using the positivity of gravitational potentials and S-deformed technique allows us to guarantee the stability… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
122
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 118 publications
(127 citation statements)
references
References 46 publications
(56 reference statements)
0
122
0
3
Order By: Relevance
“…The static black hole solution was found in Ref. [54]. The authors assumed the following metric form:…”
Section: The Action For F (R)-maxwell Gravity Ismentioning
confidence: 99%
“…The static black hole solution was found in Ref. [54]. The authors assumed the following metric form:…”
Section: The Action For F (R)-maxwell Gravity Ismentioning
confidence: 99%
“…The motivation is as follows. On the one hand, studying the black holes and their thermodynamics [64][65][66][67][68][69][70][71][72][73] in f (R) gravity has its own right. f (R) gravity, as a kind of modified gravity theory, serves as an alternative approach other than dark energy to explain the cosmic acceleration.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, adding stresstensor of a matter field to F (R) gravity, increase its difficulties. Recently, it has been shown that one can extract exact analytical solutions of F (R) theory coupled to a traceless energy momentum tensor with constant curvature scalar [18]. For example, taking into account the conformally invariant Maxwell (CIM) field as a matter source, which is traceless in arbitrary dimensions, some black objects of F (R) gravity were obtained in higher dimensions [19].…”
Section: Introductionmentioning
confidence: 99%